A time-course transcriptome analysis of wax gourd fruit development reveals predominant genes regulating taste and nutrition - Xue, Shudan; Wan, Xiaotong; Lu, Sen; Zhong, Yujuan; Xie, Dasen (Frontiers in Plant Science, 2022)
Wax gourd, which belongs to Cucurbitaceae, is an excellent plant resource with the concomitant function of both medicine and foodstuff. Its unique taste and rich nutrition are deeply accepted by consumers. However, the main flavor and nutrients are still unclear, which restricts the quality breeding process of wax gourd. Here, we discovered that monosaccharides, malic acid and citrulline affect the flavor and nutrition of wax gourd and clarified the dynamic accumulation process of these metabolites. To gain insights into the underlying predominant genes regulating accumulation of these metabolites, we performed a time-course transcriptome analysis using RNA-sequencing analysis and compared the expression of screened genes among twenty-four germplasms with different metabolites levels. In addition, the expression abundance among the homologous genes were also analyzed. Finally, a total of 8 genes related to sugar [AGA2 (Bhi03G001926), SUS (Bhi12G001032)], malic acid [MDH (Bhi12G001426, Bhi01G000427), PEPC (Bhi12G000721, Bhi09G002867), ME (Bhi01G002616)] and citrulline [ASS (Bhi02G000401)], respectively were determined. In summary, understanding the core genes influencing taste or nutrition will provide a theoretical basis for fruit quality improvement in wax gourd.